Determinants of exchange rate changes in Malaysia / Muhammad Naim Ali - Ali, Muhammad Naim (Faculty of Business and Management, 2018)
This study examines the relationships that between exchange rate index (ERI) and the determinants exchange rate changes, economic growth rate (GDP), money supply (BM), total reserve (TR), current account balance (CAB) and inflation rate (INF) from the year of 1974 to 2015 which contains yearly data. This paper applies Autoregressive Distributed Lag (ARDL) methods in order to define the statistical relationship among the variables. Besides, there are steps involved in the study begin with Autoregressive Distributed Lag (ARDL) methods and proceed with Unit Root test, ARDL Cointergration, Diagnostic Test, ARDL short run and long run elasticities. In Diagnostic Tests, some tests done to check the significant presents of autocorrelation, the normality of data distribution, model specification and heteroscedasticity. The result of this study show that there are significant relationships between the Exchange Rate Index (ERI) and the economic growth (GDP), current account balance (CAB) and inflation rate (INF) while money supply (BM) and total reserve (TR) did not have any relationship with the ERI. The conclusion for the studies shows that the GDP, CAB and INF become the factors that affecting the ER changes in Malaysia.